Basin planning & management, water quantity and quality - Mueller, David K., editor; Colorado Water Resources Research Institute, Colorado State University, publisher (Colorado State University. Libraries, 1993)
Proceedings of a symposium sponsored by the American Water Resources Association, Colorado Section held in Thornton, Colorado on March 5, 1993.
Basin planning and management, water quantity and quality
Water quantity and quality
March 1993.
Keywords: Watershed management -- Colorado -- Congresses; Water quality management -- Colorado -- Congresses; Watershed management -- Congresses